PERKEMBANGAN UPT. PERPUSTAKAAN UNIVERSITAS SYIAH KUALA, 1970-2016 - Ari Ristiawan; Mawardi ,; Husaini . (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2019)
The study, entitled "The Development Unit. Library of the University of Syiah Kuala, 1970-2016 ", this raises issues about how the development of UPT. Library of the University of Syiah Kuala in terms of facilities and infrastructure, a collection of books, visitors and the factors that influence its development. This study used a qualitative approach and using the historical method, while data collection technique using the documentation, observation and interviews. Primary sources used include document libraries and related informant interviews. Based on research that has been done, the results are as follows: (1) UPT. Library of the University of Syiah Kuala established in 1970, continue to increase in the development of a collection of books as well as facilities and infrastructure is also progressing in the needs of its visitors. The number of visitors has increased and a decreased in a visit to the library (2) Availability of the budget is the most important factor in influencing the development of facilities and infrastructure, a collection of books and visitors in UPT. Library of the University of Syiah Kuala. Keywords: Development, UPT. Syiah Kuala University Library.